Efficacy and safety of later-line targeted therapies in advanced non-small cell lung cancer with EGFR exon 20 insertion mutations: a systematic review - Wen, Qiang; Zhuang, Yue; Fu, Silv; Pan, Chunguo; Liu, Zhihua; Wang, Lei (Frontiers in Pharmacology, 2025)
BackgroundPlatinum-based chemotherapy and immune checkpoint inhibitors (ICIs) are currently regarded as the standard treatment modalities for advanced non-small cell lung cancer (NSCLC) characterized by EGFR exon 20 insertion (ex20ins) mutations; however, their efficacy is suboptimal. Recent developments in targeted therapies, including agents such as amivantamab, mobocertinib, and sunvozertinib, have shown promise in patients with pretreated ex20ins-positive NSCLC. However, a comprehensive systematic review assessing the efficacy and safety of these later-line Targeted therapies has not yet been conducted.MethodsA systematic search for studies pertaining to later-line treatment options for patients with ex20ins mutations was conducted using PubMed, Embase, and the Cochrane Library, with a cutoff date of 31 March 2025, without language restrictions. The primary endpoints of this review were the objective response rate (ORR) and disease control rate (DCR), whereas the secondary endpoints included progression-free survival (PFS), overall survival (OS), and the incidence of treatment-related adverse events (TRAEs).ResultsEleven studies were included in this analysis, with efficacy data encompassing 788 participants and safety data involving 861 participants. The pooled ORR for novel targeted therapies in the later-line setting was 41.8% (95% CI: 35.3%–48.3%), and the DCR was 85.6% (95% CI: 80.1%–91.1%). The pooled median PFS from eight studies was 8.020 months (95% CI: 7.203–8.930), and the pooled median OS from four studies was 20.804 months (95% CI: 16.713–25.896). Subgroup analysis indicated that there were differences in the pooled ORR for patients with near-loop insertions and far-loop insertions (44.4% vs. 34.5%) or patients with or without baseline brain metastasis (36.4% vs. 47.5%), although neither difference was significant (both P > 0.05). The most common all-grade TRAEs were diarrhea (66.8%),rash (66.7%), paronychia (42.0%). Among grade ≥3 events, diarrhea was the most frequently reported (10.1%), followed by rash (8.2%) and anemia (2.7%).ConclusionNovel targeted therapies demonstrate superior efficacy and acceptable safety compared to conventional later-line treatments in advanced NSCLC with EGFR ex20ins mutations, though further validation through randomized controlled trials is warranted.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251056825. No amendments were made to the registered protocol after commencement of the review. The full review protocol can be accessed on the PROSPERO database (Registration number: CRD420251056825).